2016
DOI: 10.1002/brb3.454
|View full text |Cite
|
Sign up to set email alerts
|

Deficits in Visual System Functional Connectivity after Blast‐Related Mild TBI are Associated with Injury Severity and Executive Dysfunction

Abstract: IntroductionApproximately, 275,000 American service members deployed to Iraq or Afghanistan have sustained a mild traumatic brain injury (mTBI), with 75% of these incidents involving an explosive blast. Visual processing problems and cognitive dysfunction are common complaints following blast‐related mTBI.MethodsIn 127 veterans, we examined resting fMRI functional connectivity (FC) of four key nodes within the visual system: lateral geniculate nucleus (LGN), primary visual cortex (V1), lateral occipital gyrus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 118 publications
0
32
0
Order By: Relevance
“…Unlike the more traditional method of spectral coherence, PLS separates the phase and amplitude components and can be directly interpreted in the framework of neural integration. 80 In the present study, the frequency increments used in the Morlet wavelet transformation were at 0.5 Hz for the low-frequency band (1-7 Hz) and alpha band (8-12 Hz), at 1 Hz for the beta band (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), and at 2 Hz for the gamma band . Similar to the Xcorr approach, ROIglobal FC measures were obtained using the PLS approach as the ROI-global connectivity vector with 94 elements.…”
Section: Roi-global Fc Using Roi Source Time Coursesmentioning
confidence: 75%
See 2 more Smart Citations
“…Unlike the more traditional method of spectral coherence, PLS separates the phase and amplitude components and can be directly interpreted in the framework of neural integration. 80 In the present study, the frequency increments used in the Morlet wavelet transformation were at 0.5 Hz for the low-frequency band (1-7 Hz) and alpha band (8-12 Hz), at 1 Hz for the beta band (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), and at 2 Hz for the gamma band . Similar to the Xcorr approach, ROIglobal FC measures were obtained using the PLS approach as the ROI-global connectivity vector with 94 elements.…”
Section: Roi-global Fc Using Roi Source Time Coursesmentioning
confidence: 75%
“…[33][34][35][36][37][38][39][40][41] Twenty-one of these rs-fMRI studies were concerned with blunt mTBI whereas only four were related to blast mTBI. In the four blast mTBI studies, Gilmore and colleagues found reduced FC between visual network regions and other brain areas, 23 Robinson and colleagues found decreased FC of bilateral primary somatosensory and motor cortices, 28 Han and colleagues found increased within-module FC, but decreased inter-module FC, 33 and Vakhtin and colleagues found decreased FC among various brain networks (default mode network [DMN]-basal ganglia, attention-sensorimotor, frontal-DMN, attentionfrontal, and sensorimotor-sensorimotor). 32 The reasons for these discrepant findings is unclear, but may partially relate to the use of different analytic approaches.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, ICN 1 is brain stem network, ICN 6 and 7 are visual networks, and ICN 17 is auditory network, which are all reported in the literature with decreased activation among mTBI patients. As in (Gilmore et al, 2016; Iraji et al, 2015; Stevens et al, 2012a), the visual processing circuit, including bilateral visual cortex (ICN 7), showed decreased functional connectivity; in (Iraji et al, 2015; Stevens et al, 2012b), diminished functional connectivity was also found for the motor systems (ICN 13); in (Schairer et al, 2012; Vander Werff, 2012), the mechanisms of injury to the auditory system in the mTBI was introduced and dysfunctions on auditory network were reported (ICN 17). In particular, the brainstem (Kushner et al, 1998), which has cranial nerves for eye movements and the auditory pathway, also showed decreased functional connectivity in mTBI patient group than the control group, relative to the visual and auditory networks.…”
Section: Resultsmentioning
confidence: 99%
“…Eye movement abnormalities in TBI could be related to the broad network of regions that must communicate effectively to acquire and integrate information from the visual environment 22 . Impaired eye movements have been linked to axonal injury in postmortem tissue and on diffusion tensor imaging; 23‐25 abnormal functional connectivity in chronic mTBI extends to the visual system and its interactions with higher‐order cognitive processing 26 . Importantly, the types of eye movements that are most strongly impacted by mTBI are those that most heavily rely upon effective cognitive processing, as opposed to measures of basic neuromotor function 14,18,27‐29 .…”
Section: Introductionmentioning
confidence: 99%